(untitled) (World Bulletin of Public Health, 2025)
The choice of surgical tactics for gastroduodenal ulcer bleeding remains a highly relevant challenge. Although this topic has been widely discussed in the literature, disagreements persist between advocates of active intervention and those supporting a more conservative, expectant approach. Between 2015 and 2025, a total of 1,816 patients with gastric and duodenal ulcer bleeding underwent surgery at the Andijan State Medical Institute. Individually tailored active tactics enable accurate assessment of blood loss and patient condition, precise identification of the bleeding source, and optimal surgical timing, thereby improving outcomes in ulcerative gastroduodenal bleeding through the use of organ-preserving procedures.